PENGARUH PENGGUNAAN YOUTUBE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMPN 25 BENGKULU SELATAN - Mindani Mindani (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2022)
PAI teachers there only teach or explain material from subject books. Even though there are lots of learning media that can be used in the teaching and learning process, for example, through YouTube social media.This study aims to determine how much influence the use of YouTube social media has on student learning outcomes in Islamic Religious Education subjects. Researchers took class VII to be used as research samples totaling 48 students. 24 students of class A as the control class and 24 students of class B as the experimental class. This study used quantitative research methods with a quasi-experimental approach. This study uses a test technique, Learning Implementation Plan (RPP) and documentation. The question test is aimed at students to find data on PAI learning outcomes using YouTube social media. Based on the results of the study, the variable x (use of YouTube social media) and variable y (PAI learning outcomes) was tested for the hypothesis using a linear regression formula and obtained a constant result of 81.572. This study used a sample of 24 students. Based on the calculated T, which is 8.036 and the T table is 1.717, it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence on the use of YouTube social media on the learning outcomes of class VII B students of SMPN 25 Bengkulu Selatan in PAI learning.Keywords: Youtube Social Media, Learning Outcome